The Change in the Properties of 130Xe - 130Nd Isobar States - Imad Mamdouh Ahmed (Jordan Journal of Physics, 2025)
The properties of the ground and negative parity state bands of 130Xe - 130Nd isobars have been studied. The ratio E / I has been calculated as a function of the spin (I) to determine the ground-state evolution. The ratio between the energies of the (I+2) and (I) states as a function of the spin (I) has been drawn to determine the property of the groundstate band. The odd-even staggering has been drawn to determine the difference of the energies of ground state band and negative parity band. The energy levels for the ground state band of 130Xe - 130Nd have been calculated using Bohr-Mottelson Model (BM), Interacting Boson Model (IBM-1), Interacting Vector Boson Model (IVBM) and Doma-ElGendy (D-G) relation. The energy levels of the negative parity band have been calculated using BM and IVBM models. The calculated energy levels in comparison with the experimental data indicated the quality of the fitness presented in this work. Keywords: Ground- state band; Negative parity band; E-GOS; The ratio between the energies of I+2 and I states; IBM-1; IVBM; D-G relation; Bohr and Mottelson. PACS numbers: 21.60.Ev, 21.60.Fw, 21.10.Re.